Uji Aktivitas Ekstrak Alang-Alang (Imperata cylindrica L) sebagai Peluruh Kalsium Batu Ginjal secara In Vitro - Istnaini Reiza Fatimah; Mahfuzun Bone; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Kidney stones are a disease caused by existence urine sediment in the kidneys and urinary tract which clog the urinary tract so that when urinating it causes pain. One alternative to be used to treat kidney stone disease is traditional treatment using herbal plants that are widespread in Indonesia. The plants that is widespread in Indonesia, Imperata that grow wild in forests, fields, lawns and roadside in sunny dry areas. The research was aimed to find secondary metabolites and activity of Imperata extract ethanol on calcium solubility of kidney stones. Kidney stones from the reaction between calcium chloride and potassium oxalate. The extract was obtained from the maceration process using 96% ethanol solvent. The test of secondary metabolites by adding chemical reagents to the extract and activity test by making 3 series of extract concentrations, namely 1%, 3% and 5%. 100 mg kidney stones were inserted in the extract solution than incubated for 3 hours (370C). The filtrate was measured dissolved calcium levels using a UV-Visible spectrophotometer at ? 499 nm. The result show that Imperata positive containing flavonoids, alkaloids, tanins, steroids and triterpenoids, and have an effect in dissolving kidney stone calcium in vitro where the best concentration of ethanol extract of Imperata is 5% concentration with dissolved calcium levels of 301,450 ppm.